Analysis of viscous flow properties of styrene–butadiene–styrene-modified asphalt. (30th December 2019) - Ding, Zhan; Zhang, Jing; Li, Peilong; Yue, Xiangjing; Bing, Hui
Highlights: The viscous activation energy ( E η ) and non-Newtonian index ( n ) of SBS-modified asphalt were calculated. The master curve was established to characterize the non-Newtonian flow behavior of the SBS-modified asphalts. The master curve can be used to predict asphalt viscosity at different temperatures and shear rates. The asphalt samples show inconsistent temperature sensitivity and fluid properties after SBS modification. The non-Newtonian properties of various types of asphalt vary with temperature. Abstract: Three styrene–butadiene–styrene (SBS, a block copolymer) modified asphalt samples with 5% SBS by weight were prepared using three types of common base asphalt to analyze the viscosity and viscous flow properties of SBS-modified asphalts. Rotational viscosity tests were conducted under various temperature and shear rate conditions, and the effects of the test conditions on the viscosity of the base and modified asphalt samples were analyzed. The viscous activation energy ( E η ) and non-Newtonian index ( n ) were calculated using the Arrhenius equation and the power law equation, respectively. The temperature sensitivity and fluid properties were considered relative to E η and n, respectively, based on which master curves were established to predict viscosity. The results indicate that various types of base asphalt show inconsistent temperature sensitivity and fluid properties after SBS modification. SBS can improve the temperature stability of B# asphalt; however, it has adverse effects on the A# and C# asphalts. Compared with the base asphalt, the n values of the SBS-modified asphalts are all lower than 1, indicating that the asphalt is converted from a Newtonian to non-Newtonian fluid and the non-Newtonian properties of various types of asphalt vary with temperature. Master curves can describe the responses of the SBS-modified asphalt viscosity to test the conditions that adequately predict the viscosity.